Work Culture of Devotion and Conflict Resolution Competence among Civil Servants in Public Service: An Integrative Literature Review - Epi Jama; Suryono Efendi; Rahayu Lestari; Hasanudin Hasanudin (Harmony Management: International Journal of Management Science and Business, 2026)
Public service delivery represents a central function of civil servants (ASNs) in realizing governmental objectives and fulfilling public needs. The increasing complexity of bureaucratic challenges not only requires administrative competence but also a devotion-based work culture and strong conflict management abilities. This study adopts an integrative literature review approach to synthesize research on the relationship between devotion-oriented work culture and conflict resolution competence among ASNs in public administration. Through thematic synthesis of empirical and conceptual studies, three primary themes emerge: (1) devotion as a moral dimension shaping civil service identity; (2) conflict resolution competence as an adaptive behavioral skill; and (3) integration of cultural and governance values for ethical performance. Findings reveal that devotion-oriented culture enhances civil servants’ problem-solving and ethical responsiveness, strengthening bureaucratic accountability and public trust. This paper contributes a conceptual framework linking work devotion, conflict competence, and public governance, providing implications for policy and administrative reform toward professional, responsive, and citizen-oriented public service.